Cannabis growers in the Spanish press at the beginning of the millennium - Marín Gutiérrez, Isidro (2023)
This article is the result of an investigation that analyzes the treatment that Spanish newspapers, specifically 98, gave to cannabis cultivation from January 1, 2001 to December 31, 2007. The content analysis methodology was applied. The treatment carried out by digital newspapers on this topic was quantified, analyzed and compared. The conclusions showed that the cultivation of cannabis by the Spanish digital press varies depending on the month, the year, the place of cultivation or the number of plants seized and has a criminal treatment. Specifically, more news about cannabis cultivation is produced in the months of August and September.